Hedging in Disguise: South Korea and ASEAN’s Alignment Behaviours Amid Great Powers Competition - Aini, Resi Qurrata (Thammasat Review, 2026)
This research aims to analyse the simultaneous hedging patterns employed by a state and regional institution with differing alignment positions. South Korea is a traditional ally of the US while ASEAN is a non-aligned institution. Utilizing a qualitative approach, the study employs the Causal Process Tracing (CPT) method to explain the behaviour of South Korea and ASEAN. This article identifies a kind of hedging pattern, termed “co-hedging” that can be executed concurrently by a regional institution and an extra-regional middle power amid great powers competition. This co-hedging behavior affirms the structural realist postulate that systemic pressures shape state behavior, while simultaneously integrating the constructivist perspective on the role of shared norms within multilateral platform. Despite originating from distinct alignment positions and not primarily intending to co-hedge, both South Korea and ASEAN exhibit a relatively similar pattern of power acceptance and rejection towards great powers through their shared membership in multilateral forums. While South Korea operates within a narrower hedging spectrum compared to ASEAN, they optimize their partnerships by supporting each other’s initiatives, such as the Korea–ASEAN Solidarity Initiative (KASI) and the ASEAN Outlook on the Indo-Pacific (AOIP).